PRAKTEK ABORSI KORBAN PEMERKOSAAN MENURUT ANALISIS QAWAIDH FIQHIYYAH FURU’IYYAH AL MUSYAQQAH TAJLIB AT TAISIR - Fitriani, Nur Isna (LPPM STAI Muhammadiyah Probolinggo, 2025)
In cases where continuing a pregnancy resulting from rape is considered to carry significant risks, it is often due to the fact that the act of rape itself already causes lifelong trauma. This trauma is further compounded by the presence of an unwanted pregnancy. In addition to the psychological burden, victims often face social stigma and are blamed for failing to protect themselves or their honor, which is perceived as the reason they became victims of such violence. In this study, the author uses a specific branch of fiqhiyyah principles (qawāʿid fiqhiyyah furūʿiyyah) as an analytical tool to examine this issue. The research method applied is a descriptive qualitative approach through library research. The study finds that the fiqhiyyah principle al-Masyaqqah Tajlib at-Taisir, meaning